(untitled) (Libya Journal of Geographical Studies, 2024)
Lake Balta Ramla, located in the south of the Jabel AlAkhder region, is one of the most important temporary lakes located in the south of the Mukhaili area by about 14 km, which consists in a flat land consisting of clay salt, and it forms a natural estuary for the torrential waters descending on the southern slope of the Green Mountain, the study aims to know the volume of water collected in the Ramla hatchet during the 2022-2023 season and track the stages of the lake’s receding from the day it was filled on 11/27/2022 until its depletion in the dry season on 07/03/2023, according to Follow-up satellite images of the American satellite Landsat 8 and the European satellite sentinel A2l2, the researchers used the historical method and the quantitative analytical approach based on the data of the satellite visuals of the two satellites, where the researchers analyzed data that included 21 consecutive images of the lake between the periods of filling the lake and the period of depletion, over a period of 100 days, and topographic and geological maps of the study area were used, and the image and map data was transferred to the ArcGIS environment after processing and correcting it geographically, and a geographical database was created, and the data of those was analyzed Images with the help of eos.landviewer, and using the NWDI indicator were measured